Application of The Quizizz Educational Game to Math Learning Outcomes - Zulfitria; Aryandini, Tyasti; Arif, Zainal (Education, Science, and Technology International Conference, 2024)
This article is inspired by teachers’ creative use of the educational game Quizizz to enhance student learning outcomes. It aims to gain thorough knowledge of how the cutting-edge educational game Quizizz affects mathematics learning outcomes for fifth-grade students. The study was conducted during semester 2 of January–July 2022 at SD Negeri Jatiasih X Bekasi. This descriptive qualitative research employed observational data, interviews, and documentation. Six interview subjects and all fifth graders participated in the study. The findings suggest that using Quizizz educational games improves learning outcomes, as evidenced by a significant 4.29% increase in student learning motivation and results. Thus, it can be inferred that Quizizz has the potential to enhance student learning outcomes. Future researchers and stakeholders, including school administrators, instructors, parents, and students, are expected to benefit from this study.